Determining the kinematics of trolley movement using 4 mechanical wheels - Tito, Denis; Muskhir, Mukhlidi; Mukhaiyar, Riki; Habibullah; Luthfi, Afdal (Department of Electrical Engineering Universitas Negeri Padang, 2024)
4.0 Industrial Revolution brings significant changes across various aspects of life, including the retail sector. The adoption of automation technology in supermarkets can enhance efficiency and consumer convenience. One of the challenges is the use of conventional shopping carts, which require pushing and pulling, often creating difficulties for customers with physical limitations. To address this issue, this study proposes the development of an automated robotic cart using mechanical wheels. Mecanum wheels enable dynamic movement in all directions without the need to change the wheel orientation, making them a more flexible solution compared to traditional differential wheels. The robotic cart is equipped with four 120 mm mecanum wheels and uses DC motors controlled by Pulse Width Modulation (PWM) through an H-bridge circuit and microcontroller. This technology implementation is expected to facilitate smoother cart movement and improve the shopping experience. The study presents the design and kinematic movement of the robot, demonstrating the advantages of using mecanum wheels in enhancing the mobility and flexibility of automated shopping carts